Spinel-structure CoFe2S4 as electrocatalyst for oxygen evolution reaction in alkaline medium - Ng, Khay Wen (2019)
Small molecular electrocatalysts are essential in the application of fuel cells and electrolyzers as the commitment towards the low carbon economy. The rising demand of effective and affordable catalysts for the bottleneck oxygen evolution reaction (OER) of water electrolysis has stimulated the development of catalysts from transition metal-based compounds, replacing the costly noble metal-based materials. In this report, cobalt-iron spinel sulfide CoFe2S4 particles are prepared through hydrothermal method and applied as an electrocatalyst for OER in alkaline KOH electrolyte with different pH (12.5, 13 and 13.5). The spinel structured CoFe2S4 is characterized via scanning electron microscope (SEM) imaging, x-ray diffraction (XRD) analysis and Brunaeur-Emmett-Teller (BET) method. Meanwhile, the OER activity of CoFe2S4 particles is reviewed through cyclic voltammetry (CV) measurement. The electrochemical analysis results show the increase of current density at specific applied potential as the pH of KOH increases, which deduce that the catalytic activity of CoFe2S4 is dependent on pH of the electrolyte used. Also, CoFe2S4 particles display small overpotential and a small Tafel slope in 0.3M KOH solution (pH=13.5), making it an interesting material as OER electrocatalyst in basic media.